Comparison of Direct Anterior and Lateral Approaches in Total Hip Arthroplasty: A Systematic Review and Meta-Analysis (PRISMA). Issue 50 (December 2015) - Yue, Chen; Kang, Pengde; Pei, Fuxing
Abstract : Abstract: The direct anterior approach (DAA) to total hip arthroplasty has been promoted as a minimally invasive alternative to the lateral approach, which we sought to verify by systematically reviewing and meta-analyzing the literature comparing clinical, radiographic, and surgical outcomes. Two reviewers independently searched PubMed, OVID, and Web of Science databases for randomized controlled trials (RCTs) and cohort studies comparing the DAA and lateral approach for total hip arthroplasty. Quality of RCTs was assessed using the Jadad scoring system, quality of cohort studies, using the Minors system. Data were extracted and meta-analyzed or qualitatively synthesized for primary outcomes (function, complications, and hospitalization time) and several secondary outcomes. Data were extracted from 12 trials involving 4901 arthroplasty procedures. Meta-analysis showed that DAA was associated with significantly shorter hospitalization than the lateral approach, as well as greater functional rehabilitation and lower perceived pain during the early postoperative period. On the other hand, DAA was associated with longer surgery time. The 2 approaches were associated with similar rates of perioperative surgical complications and transfusions, as well as similar radiographic analysis results. Although DAA may provide shorter hospitalization and faster recovery during the early postoperative period, the available evidence is still insufficient to conclude whether the DAA or lateral approach is superior for total hip arthroplasty. More high-quality studies and subsequent meta-analyses are needed. Abstract : Supplemental Digital Content is available in the text